Evolution of non-collinear magnetic state of exchange biased ferromagnet/normal metal/ ferromagnet/superconductor heterostructure in magnetic field studied by polarized neutron reflectometry - Khaydukov, Yu.; Morari, R.; Zdravkov, V.; Mustafa, L.; Keller, T.; Keimer, B.; Sidorenko, A. (Физика низких температур, 2017)
By using waveguide enhanced polarized neutron reflectometry we have characterized the magnetic state of exchange biased CoO x(20 nm)/Co(4 nm)/Nb(5 nm)/Co(2 nm)/Nb(25 nm)/Al₂O₃ system. Measurement allowed to determine the dependence of the inclination angles of magnetic moment of the both Co layers as a function of applied field. According to the measurement the soft Co(2 nm) layer magnetization turns towards external field in magnetic fields as small as 20 Oe. In contrast direction of magnetic moment of Co(4 nm) layer cannot be altered in magnetic fields as high as 2 kOe.